Lung angiotensin converting enzyme activity in chronically hypoxic rats. Issue 8 (August 1985) - Kay, J M; Keane, P M; Suyama, K L; Gauthier, D
Abstract : A study was carried out to test the hypothesis that the reduced lung angiotensin converting enzyme (ACE) activity which occurs in chronic hypoxia is related to the development of pulmonary hypertension rather than to hypoxia per se. Right ventricular mean systolic pressure (Prvs, mm Hg) and ACE activity (nmol/mg protein/min) in lung tissue homogenates were measured in seven groups of four rats placed in a hypobaric chamber (380 mm Hg; 51 kPa) for two to 24 days. Identical measurements were made on 11 groups of four rats, which were placed in the chamber for 24 days and then allowed to recover in room air for one to 153 days. After two days of hypoxia the mean Prvs (25.5 (SD 3.7] and the mean lung ACE activity (56 (4.6] did not differ significantly from control values. Exposure to hypoxia for four to 24 days caused a progressive increase in mean Prvs to 44.4 (5.9) and a progressive reduction in mean lung ACE activity to 34 (4.0). During recovery lung ACE activity increased and Prvs decreased, so that normal values were achieved by 15 and 56 days respectively. Decreased lung ACE activity may be related to haemodynamic factors associated with pulmonary hypertension rather than to hypoxia.